2018
DOI: 10.1002/anie.201806148
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/Rhodium Cooperative Catalysis for the Production of Aryl Aldehydes and Their Deuterated Analogues Using the Water–Gas Shift Reaction

Abstract: A novel Pd/Rh dual-metallic cooperative catalytic process has been developed to effect the reductive carbon-ylation of aryl halides in moderate to good yield. In this reaction, water is the hydride source, and CO serves both as the carbonyl source and the terminal reductant through the water-gas shift reaction. The catalytic generation of the Rh hydride allows for the selective formation of highly hindered aryl aldehydes that are inaccessible through previously reported reductive carbonylation protocols. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Reducing the amount of TBADT or thiol 7a slightly decreased the deuterium incorporation percentage (entries 8 and 9). Control experiments showed that the reaction failed to proceed in the absence of the HAT photocatalyst, the thiol catalyst, or light (entries [10][11][12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the amount of TBADT or thiol 7a slightly decreased the deuterium incorporation percentage (entries 8 and 9). Control experiments showed that the reaction failed to proceed in the absence of the HAT photocatalyst, the thiol catalyst, or light (entries [10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…The development of an efficient protocol for constructing formyl-deuterated aromatic aldehydes can be expected to increase the availability of deuterated lead compounds. Aromatic aldehydes selectively labeled at the formyl position are traditionally produced from the corresponding esters by means of reduction with LiAlD 4 followed by oxidation, 9 from the corresponding amides by reaction with deuterated Schwartz's reagent (obtained from LiAlD 4 ), 10 from aryl halides via Pd/Rhcocatalyzed reductive carbonylation, 11 or from carboxylic acids via deoxygenative deuteration with synergistic photoredox and organic catalysis (Scheme 1A). 12 In terms of atom-and stepeconomy, the ideal protocol for preparing deuterated Scheme 1 Strategies for synthesizing deuterated aldehydes; (A) previous methods to produce deuterated aldehydes through FG transformation; (B) hydrogen isotope exchange (HIE) to produce deuterated aldehydes; (C) hypothesis for the proposed deuteration; (D) our work.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic aldehydes were selected as the target for site-selective deuteration for its synthetic importance at the center of functional group transformations. To date, several strategies have been developed for the generation of the deutero-formyl group of aromatic aldehydes (Scheme a), including reductive carboxylation of aromatic halides, site-selective hydrogen isotope exchange (HIE), and reduction of carboxylic acid with deuterated reductants or deoxygenators . The regioselective aryl-deuteration of aromatic aldehyde had rarely been studied, despite the ortho -HIE of compounds with various directing groups such as amides, carboxyl, sulfonyl, phosphonyl groups, and nitrogen-containing heterocycles .…”
Section: Introductionmentioning
confidence: 99%
“…So far, this concept has been used both in homogeneous and heterogeneous catalysis, yet mainly in hydroformylation and hydrogenation reactions including nitro reduction, reductive amination, hydrogenation of carbonyls and alkenes. 10 However, due to the high-temperature requirement (>180 °C), applications in organic synthesis remain largely underdeveloped. 11 …”
Section: Introductionmentioning
confidence: 99%